Kepuasan Pasien Terhadap Layanan Puskesmas BLUD di Kota Semarang - Chriswardani Suryawati; Nurhasmadiar Nandini; Novia Handayani (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
Primary Health Centre (PHC) is one of the public institution which have important role to provide health care services to the community. According to Regulation of Semarang Major no. 13 year 2016 about Governance Pattern of Local Public Service Institution (BLUD) of Puskesmas, since 2017 PHC in Semarang transformed into BLUD PHC which enable PHC to be more flexible, productive, efficient, and effective on managing their resources and finance. This research objective was to identify patient satisfaction of BLUD PHC in Semarang. This was quantitative research with cross-sectional design and research variables are tangible, reliability, responsiveness, assurance, empaty, dan patient’s satisfaction. Respondents were 140 patients of BLUD PHC in Semarang City: Bulu Lor, Gayamsari, Pudakpayung, Bangetayu, Halmahera, Kedungmundu, dan Mangkang. Result showed that most of the patient satisfied with the health care services in PHC. From all of the indicators, more than 80% respondents stated that they were satisfied with the services in PHC. The highest score was on responsiveness aspect, which 95.0% patient scored high on the PHC responsiveness. It could be because PHC already maximize their resources to provide high quality health care services.